Oligo(phenylenevinylene) hybrids and self-assemblies: versatile materials for excitation energy transfer - Praveen, Vakayil K; Ranjith, Choorikkat; Bandini, Elisa; Ajayaghosh, Ayyappanpillai; Armaroli, Nicola (Chemical Society reviews, 2014)
Oligo(phenylenevinylene)s (OPVs) are extensively investigated π-conjugated molecules that exhibit absorption and fluorescence in the UV-Vis spectral region, which can be widely tuned by chemical functionalisation and external control ( e.g. solvent, temperature, pH). Further modulation of the optoelectronic properties of OPVs is possible by supramolecular aggregation, primarily driven by hydrogen bonding or π-stacking interactions. In recent years, extensive research work has been accomplished in exploiting the unique combination of the structural and electronic properties of OPVs, most of which has been targeted at the preparation of molecules and materials featuring photoinduced energy transfer. This review intends to offer an overview of the multicomponent arrays and self-assembled materials based on OPV which have been designed to undergo energy transfer by means of a thorough choice of excitation donor-acceptor partners. We present a few selected examples of photoactive dyads and triads containing organic moieties ( e.g. fullerene, phenanthroline) as well as coordination compounds (Cu( i ) complexes). We then focus more extensively on self-assembled materials containing suitably functionalised OPVs that lead to hydrogen bonded aggregates, helical structures, gels, nanoparticles, vesicles, mesostructured organic-inorganic hybrid films, functionalised nanoparticles and quantum dots. In most cases, these materials exhibit luminescence whose colour and intensity is related to the efficiency and direction of the energy transfer processes. The engineering of the nanostructure of OPV based self-assemblies allows control of photoinduced energy transfer processes, leading to materials exhibiting tunable luminescence colours, including white.